NICE DRINK MINUMAN BERBAHAN DASAR LOKAL KHAS DESA CISAAT KABUPATEN SUBANG - Mulyati; Muhammad Faesal; Jaka Marsita (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2022)
Abstract The 2022 Covid-19 pandemic has begun to subside, one of the countries that is actively voicing a movement for improvement is Indonesia through the tagline "Recover Together, Recover Stronger" at the G20 meeting. Cisaat Village as one of the best tourist destinations ranked 3rd nationally also does not remain silent. starting to rearrange everything that is needed before the tourist destination is busy being visited again by tourists. Starting from homestays, tourist attractions, supporting facilities, administrative requirements to typical village culinary delights are also prepared. Jakarta State University, which has been accompanying Cisaat Village since 2018, feels compelled to help village communities in the "Recovery" mission. The Family Welfare Education Study Program as one of the study programs under the auspices of the Faculty of Engineering, Jakarta State University is preparing a community service program with the theme “Training for Products and Businesses of Beverages Made from Local Raw Materials as an Alternative Business for Homestay Managers in the Cisaat Educational Tourism Village, Subang Regency -West Java". The program focuses on developing the typical culinary delights of Cisaat Village, especially in terms of the Sari Nanas (Sarinas) drink that already existed and then developed so that it can be an alternative business and welcome drink to be served to guests staying at the homestay. This training gave birth to 3 new flavors that enriched the existing variants of pineapple juice. The resulting flavors include Nasreh (Pineapple Lemongrass), Mojito and Pinaple Ice Tea. Based on the preference test on the three variants, it showed that the pineapple tea flavor variant was the most preferred, followed by the mojito and nasreh flavors. Abstrak Badai Pandemi covid-19 tahun 2022 mulai mereda, salah satu negara yang sedang gencar menyuarakan gerakan perbaikan adalah Indonesia lewat tagline “Recover Together, Recover Stronger” dalam pertemuan G20. Desa Cisaat sebagai salah satu destinasi wisata terbaik peringkat 3 nasional juga tidak tinggal diam. mulai menata kembali segala hal yang diperlukan sebelum destinasi wisata tersebut ramai dikunjungi kembali oleh wisatawan. Mulai dari homestay, atraksi wisata, fasilitas pendukung, persyaratan administratif hingga kuliner khas desa juga dipersiapkan. Universitas Negeri Jakarta yang sudah sejak tahun 2018 mendampingi Desa Cisaat merasa terpanggil untuk membantu masyarakat desa dalam misi “Recovery” tersebut. Program Studi Pendidikan Kesejahteraan Keluarga sebagai salah satu program studi yang berada dibawah naungan Fakultas Teknik Universitas Negeri Jakarta mempersiapkan suatu program pengabdian kepada masyarakat dengan tema “Pelatihan Produk Dan Usaha Minuman Berbahan Baku Lokal Seba gai Alternatif Usaha Bagi Pengelola Homestay Di Desa Wisata Edukasi Cisaat Kabupaten Subang-Jawa Barat”. Program tersebut berfokus pada pengembangan kuliner khas Desa Cisaat khususnya dari sisi minuman khas Sari Nanas(Sarinas) yang telah ada sebelumnya kemudian dikembangkan sehingga bisa menjadi alternatif usaha dan minuman selamat datang yang akan disajikan pada tamu yang menginap di homestay. Pelatihan ini melahirkan 3 rasa baru yang memperkaya varian minuman sari nanas yang sebelumnya telah ada. Varian rasa yang dihasilkan antara lain Nasreh (Nanas Serai), Mojito dan Pinaple Ice Tea. Berdasarkan uji kesukaan pada ketiga varian menunjukan bahwa varian rasa pineapple tea paling banyak disukai dilanjutkan oleh rasa mojito dan nasreh.